Academician Alexander Nikolaevich Bakulev (1890–1967) (on the 130th anniversary of the birthday) - A. A. Kurygin; I. S. Tarbaev; V. V. Semenov (Вестник хирургии имени И.И. Грекова)
The article is devoted to academician of the USSR Academy of Medical Sciences A. N. Bakulev-the founder of cardiovascular surgery in the USSR and the first director of the Research Institute of thoracic surgery (since 1961, cardiovascular surgery), who made a significant contribution to the development of issue of stomach and esophageal cancer, x-ray contrast diagnostics and puncture treatment of brain abscesses, ways of treatment of bullet wounds of the skull, spine, brain.